Beating 1 Sievert: Optimal Radiation Shielding of Astronauts on a Mission to Mars - M. I. Dobynde; Y. Y. Shprits; A. Y. Drozdov; J. Hoffman; Ju Li (Space Weather)
Abstract Space radiation is one of the main concerns in planning long‐term human space missions. There are two main types of hazardous radiation: solar energetic particles (SEP) and galactic cosmic rays (GCR). The intensity and evolution of both depends on solar activity. GCR activity is most enhanced during solar minimum and lowest during solar maximum. The reduction of GCRs is alagging behind solar activity only by 6–12 month. SEP probability and intensity are maximized during solar maximum and are minimized during solar minimum. In this study, we combine models of the particle environment arising due to SEP and GCR with Monte Carlo simulations of radiation propagation inside a spacecraft and phantom. We include 28 fully ionized GCR elements from hydrogen to nickel and consider protons and nine ion species to model the SEP irradiation. Our calculations demonstrate that the optimal time for a flight to Mars would be launching the mission at solar maximum, and that the flight duration should not exceed approximately 4 years.